2009
DOI: 10.1542/peds.2008-3653
|View full text |Cite
|
Sign up to set email alerts
|

A Videolaryngoscopy Technique for the Intubation of the Newborn: Preliminary Report

Abstract: This new technique and technology show promise to improve airway management, evaluation, and teaching. Future research to validate improved intubation success in difficult airways and in teaching situations is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…Videolaryngoscopy has shown its clinical usefulness in infants as small as 530 g [44]. Videolaryngoscopy incorporates a fiberoptic camera lens into the light source of a laryngoscope blade, effectively positioning the laryngoscopist's eye at the tip of the blade, expanding the viewing angle offered by the direct laryngoscope [45].…”
Section: Alternative Methods Of Intubating Neonatesmentioning
confidence: 99%
“…Videolaryngoscopy has shown its clinical usefulness in infants as small as 530 g [44]. Videolaryngoscopy incorporates a fiberoptic camera lens into the light source of a laryngoscope blade, effectively positioning the laryngoscopist's eye at the tip of the blade, expanding the viewing angle offered by the direct laryngoscope [45].…”
Section: Alternative Methods Of Intubating Neonatesmentioning
confidence: 99%
“…For larger infants, both instruments produce a very useful image and can facilitate intubation when used by experienced operators. 76 Environment All of the above interventions can be better accomplished in an environment conducive to critical care. The resuscitation suite should be thought of as a place where the very best equipment is needed.…”
Section: Intubationmentioning
confidence: 99%
“…16 Video-assisted intubation is increasingly recognized as the method of choice in teaching ETI because of the magnified view it offers simultaneously to both trainees and supervisors. 17 Mannequin studies have reported improved success rates of ETI and decreased time to intubation with the VL. [18][19][20] Clinical studies are limited to preliminary experience where infants as small as 530 g were intubated with the VL.…”
mentioning
confidence: 99%
“…[18][19][20] Clinical studies are limited to preliminary experience where infants as small as 530 g were intubated with the VL. 17 To the best of our knowledge, there are no published human studies comparing VL to CL for acquiring the skill of neonatal ETI in the NICU. 21 This study aimed to assess whether VL is superior to CL in acquiring skill in neonatal ETI in the NICU and whether the skill acquired with the VL is transferable to use of the CL.…”
mentioning
confidence: 99%